2017
DOI: 10.1002/ieam.1902
|View full text |Cite
|
Sign up to set email alerts
|

From the sea to the laboratory: Characterization of microplastic as prerequisite for the assessment of ecotoxicological impact

Abstract: This is 1 of 15 invited commentaries in the series "Current Understanding of Risks Posed by Microplastics in the Environment." Each peer-reviewed commentary reflects the views and knowledge of international experts in this field and, collectively, inform our current understanding of microplastics fate and effects in the aquatic environment. ABSTRACTThe presence of microplastic (MP) in the aquatic environment is recognized as a global-scale pollution issue. Secondary MP particles result from an ongoing fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…However, most studies assessing the toxicity of microplastics use a single-sized spherical model PMP (Phuong et al, 2016) for exposure experiments, although SMP are reported to have higher abundance in natural environments (Connors et al, 2017;Potthoff et al, 2017). In a recent study, Ogonowski et al (2016) compared the toxicity of PMP and artificially weathered SMP on processes like feeding, growth as well as reproduction, during chronic exposure to D. magna and found that while PMP had limited impacts, exposure to SMP resulted in reduced reproductive output.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies assessing the toxicity of microplastics use a single-sized spherical model PMP (Phuong et al, 2016) for exposure experiments, although SMP are reported to have higher abundance in natural environments (Connors et al, 2017;Potthoff et al, 2017). In a recent study, Ogonowski et al (2016) compared the toxicity of PMP and artificially weathered SMP on processes like feeding, growth as well as reproduction, during chronic exposure to D. magna and found that while PMP had limited impacts, exposure to SMP resulted in reduced reproductive output.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary microplastics are formed by the environmental degradation of larger plastic debris (Andrady, 2011), mainly by wave action and abrasion, UV-B radiation and temperature changes (Andrady, 2011;Browne et al, 2007). To date, however, the majority of studies have used primary microplastics to study adverse impacts, although secondary microplastics are more abundant in natural environments (Connors et al, 2017;Phuong et al, 2016;Potthoff et al, 2017). Ogonowski et al (2016) was the first study to compare the toxicity of primary and secondary microplastics on life history parameters such as feeding, growth and reproductive capacity during chronic exposure to D. magna.…”
Section: Introductionmentioning
confidence: 99%
“…For the detection and identification of dumped warfare relicts, ROTV and Gliders can be deployed, while the concentrations of leaking contaminants in the water can be monitored employing Active Biomonitoring using Blue Mussels or Passive Samplers. Regarding microplastics, the constant fragmentation and the large diversity within types of particles cannot be adequately addressed by a single method (Potthoff et al, 2017). Therefore, novel methods can be combined, e.g., by sampling larger particles using the Manta Trawl and complement these data by Rocket filtration samples and Sediment Corers.…”
Section: Coverage Of Gaps By the Novel Methodsmentioning
confidence: 99%